Epistatic interaction of PDE4DIP and DES mutations in familial atrial fibrillation with slow conduction. Issue 10 (29th July 2021) - Abou Ziki, Maen D.; Bhat, Neha; Neogi, Arpita; Driscoll, Tristan P.; Ugwu, Nelson; Liu, Ya; Smith, Emily; Abboud, Johny M.; Chouairi, Salah; Schwartz, Martin A.; Akar, Joseph G.; Mani, Arya
Abstract: The genetic causes of atrial fibrillation (AF) with slow conduction are unknown. Eight kindreds with familial AF and slow conduction, including a family affected by early‐onset AF, heart block, and incompletely penetrant nonischemic dilated cardiomyopathy (DCM) underwent whole exome sequencing. A known pathogenic mutation in the desmin ( DES ) gene resulting in p.S13F substitution (NM_001927.3:c.38C>T) at a PKC phosphorylation site was identified in all four members of the kindred with early‐onset AF and heart block, while only two developed DCM. Higher penetrance for AF and heart block prompted a genetic screening for DES modifier(s). A deleterious mutation in the phosphodiesterase‐4D‐interacting‐protein ( PDE4DIP ) gene resulting in p.A123T substitution (NM_001002811:c.367G>A) was identified that segregated with early‐onset AF, heart block, and the DES mutation. Three additional novel deleterious PDE4DIP mutations were identified in four other unrelated kindreds. Characterization of PDE4DIP A123T in vitro suggested impaired compartmentalization of PKA and PDE4D characterized by reduced colocalization with PDE4D, increased cAMP activation leading to higher PKA phosphorylation of the β2‐adrenergic‐receptor, and decreased PKA phosphorylation of desmin after isoproterenol stimulation. Our findings identify PDE4DIP as a novel gene for slow AF and unravel its epistatic interaction with DES mutations in development of conduction disease and arrhythmia. Abstract : PDE4DIP anchors PDE4D and PKA in proximity to the Golgi apparatus and cytoskeletal network, however mutant PDE4DIP p.A123T results in loss of colocalization with PDE4D and reduced PDE4D stability which leads to increased cAMP close to the plasma membrane with resultant increase in PKA mediated phosphorylation of ß2AR, and less PKA phosphorylation of desmin.